2016
DOI: 10.1002/reg2.61
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of planarian eye regeneration

Abstract: While tissue regeneration is typically studied using standard injury models, in nature injuries vary greatly in the amount and location of tissues lost. Planarians have the unique ability to regenerate from many different injuries (including from tiny fragments with no brain), allowing us to study the effects of different injuries on regeneration timelines. We followed the timing of regeneration for one organ, the eye, after multiple injury types that involved tissue loss (single‐ and double‐eye ablation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(69 reference statements)
0
12
0
3
Order By: Relevance
“…We next examined the regenerative properties of pre-existing versus supernumerary eyes generated by notum RNAi. Resection of normal planarian eyes results in eye regeneration over approximately 2 weeks ( Deochand et al, 2016 ; LoCascio et al, 2017 ). In notum(RNAi) animals, resection of newly formed supernumerary eyes consistently resulted in regeneration of new eyes in the same position.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the regenerative properties of pre-existing versus supernumerary eyes generated by notum RNAi. Resection of normal planarian eyes results in eye regeneration over approximately 2 weeks ( Deochand et al, 2016 ; LoCascio et al, 2017 ). In notum(RNAi) animals, resection of newly formed supernumerary eyes consistently resulted in regeneration of new eyes in the same position.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). For these experiments, we used an eye ablation technique we previously developed that removes the eyes without disturbing the underlying brain tissues ( Deochand et al, 2016 ). We found that sham surgery controls (where two pieces of anterior tissue outside the eye field were excised) displayed similar responses to uninjured wild-type worms for both green ( P =0.98, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Double eye ablations and sham ablations were performed as previously described ( Deochand et al, 2016 ). After 24 h, behavioral responses to green and near-UV light were tested and analyzed using the avoidance assay described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avaliando a capacidade de formação de brotos e raízes em segmentos nodais, Santos et al (2006) utilizaram diferentes combinações de BAP e ANA em meio de cultura WPM contendo 800 mg L -1 de PVP, 30 mg L -1 de sacarose, 7 mg L -1 de ágar e carvão ativado (0 g L -1 e 4 g L -1 ). De acordo com estes autores melhores brotações foram obtidas com 0,05 mg L -1 de ANA combinada 0,75 mg L -1 de BAP (média de 6 brotações por explante), induzindo maior número de gemas por explante (17,4), o que proporcionou a maior taxa de multiplicação (8,7). is a fruit rich in bioactive compounds.…”
Section: Piranda Et Al 2013 Revisão De Literaturaunclassified